Effects of in ovo Inoculation of Multi-Strain Lactobacilli on Cytokine Gene Expression and Antibody-Mediated Immune Responses in Chickens - Alizadeh, Mohammadali; Shojadoost, Bahram; Astill, Jake; Taha-Abdelaziz, Khaled; Karimi, Seyed Hossein; Bavananthasivam, Jegarubee; Kulkarni, Raveendra R.; Sharif, Shayan (Frontiers in Veterinary Science, 2020)
This study was conducted to investigate the effects of various doses of a multi-strain lactobacilli mixture (Lactobacillus salivarius, Lactobacillus reuteri, Lactobacillus crispatus, and Lactobacillus johnsonii) on the innate and adaptive immune responses in broiler chickens. At embryonic day eighteen, 200 eggs were injected with PBS, or three different doses of a multi-strain lactobacilli mixture (1 × 105, 1 × 106, and 1 × 107 CFU/egg, P1, P2, and P3 respectively) along with a group of negative control. On days 5 and 10 post-hatch, cecal tonsil, bursa of fabricius, and spleen were collected for gene expression and cellular analysis. On days 14 and 21 post-hatch, birds were immunized intramuscularly with both sheep red blood cells (SRBC) and keyhole limpet hemocyanin (KLH). Serum samples were collected on days 0, 7, 14, and 21 after primary immunization. The results demonstrated that lactobacilli inoculation increased the splenic expression of cytokines, including interferon (IFN)-α, IFN-β, IFN-γ, interleukin (IL)-8, and IL-12 on day 5 post-hatch compared to the control group (PBS). However, in cecal tonsils, lactobacilli treatment downregulated the expression of IL-6 on day 5 post-hatch and IL-2 and IL-8 on day 10 post-hatch. No significant differences were observed in the expression of cytokine genes in the bursa except for IL-13 which was upregulated in lactobacilli-treated groups P2 and P3 on days 5 and 10 post-hatch. Flow cytometry analysis showed that the percentage of KUL01, CD4+ and CD8+ splenocytes was not affected by treatments. In addition, no significant differences were observed for antibody titers against SRBC. However, lactobacilli treatment (P1, P2, and P3) was found to increase IgM titers on day 21 post-primary immunization compared to controls. Furthermore, in ovo injection of the highest dose of probiotics (1 × 107, P3) increased serum IgG titers against KLH on day 7 post-primary immunization. In conclusion, this study demonstrated that that in ovo administration of lactobacilli can improve antibody-mediated immune responses and differentially modulate cytokine expression in mucosal and systemic lymphoid tissues of chickens.